2009
DOI: 10.1186/1471-2407-9-8
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 tissue expression and plasma levels in patients with ovarian cancer

Abstract: BackgroundYKL-40 (chitinase-3-like-1) is a member of "mammalian chitinase-like proteins". The protein is expressed in many types of cancer cells and the highest plasma YKL-40 levels have been found in patients with metastatic disease, short recurrence/progression-free intervals, and short overall survival. The aim of the study was to determine the expression of YKL-40 in tumor tissue and plasma in patients with borderline ovarian tumor or epithelial ovarian cancer (OC), and investigate prognostic value of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 28 publications
(47 reference statements)
2
60
2
1
Order By: Relevance
“…Nevertheless, YKL-40 was mainly secreted by tumor-associated macrophages, monocytes, neutrophils, and tumor cells (5). A number of studies have suggested that YKL-40 was highly expressed in many solid tumors, such as primary colorectal cancer (6), metastatic breast cancer (7), cervical cancer (8), endometrial carcinoma (9), recurrent ovarian cancer (10), and epithelial ovarian cancer (EOC) (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, YKL-40 was mainly secreted by tumor-associated macrophages, monocytes, neutrophils, and tumor cells (5). A number of studies have suggested that YKL-40 was highly expressed in many solid tumors, such as primary colorectal cancer (6), metastatic breast cancer (7), cervical cancer (8), endometrial carcinoma (9), recurrent ovarian cancer (10), and epithelial ovarian cancer (EOC) (11).…”
mentioning
confidence: 99%
“…A retrospective clinical study of patients with different types of solid tumors indicated that the serum level of YKL-40 was elevated in patients compared to healthy subjects and the www.bjournal.com.br Braz J Med Biol Res 43(12) 2010 highest serum YKL-40 levels were detected in patients with advanced cancer and with the poorest prognosis (15). It has been suggested that YKL-40 is a better biomarker for the diagnosis of early-stage EOC than CA125 and CA15-3 (11). High YKL-40 expression has been reported in cancer cells and in preoperative blood from patients with borderline tumors and EOC (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck [18,22,62] Lung cancer (small cell carcinoma) Lung [133,134] Breast cancer Breast Colorectal cancer Colon [20,132] Kidney tumor Kidney [132,142,143] Hepatocellular carcinoma Liver [21,66] Ovarian tumor, endometrial cancer Ovary [55][56][57][58][59][60][61]133,138,139] Primary prostate cancer Prostate [23,63,144] Metastatic prostate cancer Papilloma thyroid carcinoma, thyroid tumor Thyroid [136,145] Extracellular myxoidchondrosarcoma Bone [146] Multiple myeloma Bone marrow [147,148] Hodgkin's lymphoma Lymph node [65] Malignant melanoma Melanocyte [18,64] Myxoid liposarcoma Fat cells [146] 5252 ISSN 1007-9327 CN 14-1219/R World J Gastroenterol November 14, 2009 Volume 15 Number 42…”
Section: Glioma Oligodendroglioma Glioblastomamentioning
confidence: 99%
“…Therefore, it is reasonable to predict that the serum level of CHI3L1 can be a reliable marker of progression of certain kinds of tumors and of a "bad prognosis" in patients with certain types of malignant tumors [18] . Many clinical laboratories have reported that CHI3L1 could be used as a novel tumor marker for ovarian cancer [55,56] , small cell lung cancer [22] , metastatic breast cancer [57] , and metastatic prostate cancer [23] . In addition, several groups have reported that CHI3L1 is one of the most significant prognosis markers for cervical adenocarcinoma [58] , recurrent breast cancer [4] and metastatic breast cancer [21] , as well as advanced stages of breast cancer [59] .…”
Section: Expression Of Chi3l1 In Various Solid Tumorsmentioning
confidence: 99%